The effect of dietary energy density on growth performance of finishing swine treated with porcine somatotropin - G R Stoner; B R Schricker; Jim L Nelssen; Robert D Goodband; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1989)
A growth study (60 barrows averaging 125.4 lb) was conducted to evaluate the effect of dietary energy density on growth performance of finishing pigs treated with porcine somatotropin (pST). Barrows were blocked on weight and allotted randomly to pens (2 barrows/pen, 5 pens/treatment). Barrows were injected daily with 4 mg pST and fed six experimental diets with four energy densities (1.37, 1.48, 1.60, or 1.71 Meal ME/lb) and four lysinc:energy ratios (4.0, 3.7, 3.4, or 3.2 g lysine/Mcal ME). Diets were formulated to contain at least 200% of NRC (1988) recommendations for essential nutrients. Increasing dietary energy density and adjusting the lysine:energy ratio to maintain 3.4 g lysine/Mcal ME decreased average daily feed intake and improved feed efficiency, but did not affect average daily gain. Increasing dietary energy density without adjusting the lysine:energy ratio increased average daily gain, decreased average daily feed intake, and improved feed efficiency linearly. These results indicate that finishing pigs injected daily with 4 mg pST and consuming 30 g lysine per day require approximately 9 Meal ME per day to optimize growth performance and efficiency.; Swine Day, Manhattan, KS, November 16, 1989
Keywords: Swine day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-163-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 581; Swine; Pig; Porcine somatotropin; Energy; Growth performance